Low-viscosity high-strength thermotropic liquid crystal polymer and preparation method thereof

By introducing 3-ethoxy-4-hydroxybenzoic acid (EHA) into TLCP resin, the melting point and melt viscosity are reduced, solving the problems of high-temperature processing and fragile weld lines of traditional TLCP. This achieves high fluidity and toughness at low temperatures, making it suitable for high-precision electronic components and medical devices.

CN121248908APending Publication Date: 2026-01-02SHANDONG NON METALLIC MATERIAL RESEARCH INSTITUTE +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511508104.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-22
Publication Date
2026-01-02

AI Technical Summary

Technical Problem

Traditional thermotropic liquid crystal polymers (TLCPs) have high energy consumption and equipment wear and tear, risk of material thermal degradation, insufficient melt flow leading to difficulty in mold filling, and high brittleness and low weld line strength, making them difficult to apply to heat-sensitive components and complex microstructures.

Method used

Traditional TLCP resins were modified using 3-ethoxy-4-hydroxybenzoic acid (EHA). By adjusting the monomer ratio and polymerization process, the melting point and melt viscosity were reduced, thereby improving the processability and toughness of the material.

Benefits of technology

It achieves high fluidity and good toughness at low processing temperatures, improves material reliability and weld line strength, reduces injection pressure and mold wear, and is suitable for high-precision applications such as 5G micro connectors and wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a low-viscosity high-strength thermotropic liquid crystal polymer and a preparation method thereof, and belongs to the technical field of polymer materials. According to the invention, a part of p-hydroxybenzoic acid (HBA) monomer in a polymer main chain is replaced by 3-ethoxy-4-hydroxybenzoic acid (EHA) for copolymerization modification. EHA is taken as a raw material, the regularity of an original p-hydroxybenzoic acid chain segment is destroyed by using an ethyoxyl side chain in an EHA molecule, so that the melt viscosity is remarkably reduced, the fluidity is improved by 30% or above, and meanwhile, excellent mechanical properties and dimensional stability of the material are still kept. The modified thermotropic liquid crystal polymer has improved processability, is suitable for thin-wall and complex precise injection molding and shows enhanced toughness and impact resistance, and the notch impact strength of the thermotropic liquid crystal polymer is improved by 15-30%. The technical problems that a traditional thermotropic liquid crystal polymer is high in processing temperature, fragile in weld line and the like are effectively solved, and the obtained material is particularly suitable for the high-precision application fields of 5G connectors, miniature electronic elements, medical instrument parts and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a low-viscosity, high-strength thermotropic liquid crystal polymer and its preparation method. Background Technology

[0002] Thermotropic liquid crystalline polymers (TLCPs) are widely used in high-end fields such as precision electronic connectors, fiber optic communication components, and high-temperature sensors due to their excellent high strength, high modulus, low coefficient of thermal expansion, chemical resistance, and self-reinforcing properties. Traditional TLCPs are typically prepared by copolymerizing p-hydroxybenzoic acid (HBA) with 2-hydroxy-6-naphthoic acid (HNA) and terephthalic acid (TA). However, these HBA-based TLCPs have performance drawbacks: 1. The processing temperature is too high. Due to their highly regular molecular chains and strong crystallinity, the melting temperature (Tm) typically needs to reach 280-350℃. This high-temperature processing leads to high energy consumption and equipment wear, increases the risk of thermal degradation (generating pores and charring), and makes them difficult to apply to heat-sensitive components (such as precision parts containing metal inserts). 2. Insufficient melt fluidity and high melt viscosity make mold filling difficult, easily leading to defects such as material shortage and flow marks when molding thin-walled parts with a wall thickness ≤0.3mm or complex microstructures. 3. High brittleness and low weld line strength: High crystallinity and molecular chain orientation result in poor impact resistance. Furthermore, the molecular chains at the melt front junctions are difficult to entangle, causing a sharp drop in strength in the weld line area (only 50-70% of the bulk strength), becoming a major cause of structural component failure.

[0003] While improvements such as adding plasticizers or inorganic fillers can reduce processing temperature or improve material toughness to some extent, they often come at the cost of decreased mechanical strength, dimensional stability, or heat resistance. Therefore, the industry urgently needs to develop a new material that combines low processing temperature, high fluidity, and good toughness without sacrificing the intrinsic properties of TLCP. Summary of the Invention

[0004] In view of the above-mentioned prior art, the purpose of this invention is to provide a low-viscosity, high-strength thermotropic liquid crystal polymer and its preparation method. 3-ethoxy-4-hydroxybenzoic acid (EHA) is used to modify traditional TLCP resin, aiming to effectively improve the resin's processability within a controllable strength loss range.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a low-viscosity, high-strength thermotropic liquid crystal polymer, which is polymerized from monomers comprising: p-hydroxybenzoic acid, 3-ethoxy-4-hydroxybenzoic acid, and 2-hydroxy-6-naphthoic acid.

[0006] Furthermore, 3-ethoxy-4-hydroxybenzoic acid accounts for 1-5 mol of the total structural units of the polymer backbone.

[0007] Furthermore, in molar percentage, the ratio of p-hydroxybenzoic acid to 2-hydroxy-6-naphthoic acid in the polymer backbone structural unit is (68-73):(22-26).

[0008] p-Hydroxybenzoic acid (HBA) serves as a mesocrystalline unit that provides the main properties of the polymer, while 2-hydroxy-6-naphthoic acid (HNA) and 3-ethoxy-4-hydroxybenzoic acid serve as transition units to reduce the order of the molecular chain and improve processability.

[0009] Furthermore, the performance indicators of the low-viscosity, high-strength thermotropic liquid crystal polymer are as follows: notched cantilever beam impact strength of 20.4-50.2 J / m, tensile strength of 92.3-121.4 MPa, and melt viscosity of 3.61-8.04 Pa·s.

[0010] A second aspect of the present invention provides a method for preparing the aforementioned low-viscosity, high-strength thermotropic liquid crystal polymer, comprising the following steps: (1) Mix the monomer and catalyst evenly according to the ratio, and add acetic anhydride; (2) Heating and stirring are carried out in an inert atmosphere until the solid material is completely melted. The temperature is maintained to carry out the acetylation reaction. (3) Continue heating to promote the forward polymerization reaction and obtain the prepolymer; (4) The prepolymer is added to a solid-phase thickening device to carry out a thickening reaction, and a low-viscosity, high-strength thermotropic liquid crystal polymer is obtained.

[0011] Furthermore, in step (1), the catalyst used is antimony acetate, and the amount of antimony acetate added is 200-400 mg / kg compared to the total mass of the monomer used; the molar ratio of the added acetic anhydride to the monomer is (0.8-1.2):1.

[0012] The amount of acetic anhydride used is 80-120 mol% of the total polymer monomers, and the acetylation temperature is 150℃. The acetylation reaction acetylates the hydroxyl groups on the benzene and naphthalene rings, making them more susceptible to transesterification with carboxyl groups, thus promoting polymerization. Therefore, the amount of acetic anhydride used should be controlled at around 100 mol%.

[0013] Furthermore, in step (2), 99.9% high-purity nitrogen is used to maintain an inert atmosphere, the stirring rate is 20-100 rpm / min, and the temperature is maintained at 140-160℃ for 0.5-2 hours.

[0014] Further, in step (3), the temperature is increased, and the reaction is carried out at 190-210℃ for 0.5-2 hours, 210-230℃ for 0.5-2 hours, and 270-290℃ for 1-3 hours. Then the temperature is increased to 310-330℃, the vacuum is evacuated to a vacuum degree of -0.1 MPa, and the reaction is continued for 0.5-2 hours to obtain the prepolymer.

[0015] The final temperature for heating is 320℃. TLCP is generally synthesized at relatively high temperatures. The melting point of TLCP resin without 3-ethoxy-4-hydroxybenzoic acid modification is around 280-350℃. After modification, the melting point is lowered. Therefore, the key reaction temperature is set at 320℃.

[0016] Furthermore, in step (4), the prepolymer is subjected to a vacuum reaction at 190-210°C for 12-36 hours in the solid phase thickening device.

[0017] Furthermore, in step (4), after the thickening reaction, the melt viscosity of the low-viscosity, high-strength thermotropic liquid crystal polymer is ≥3.0 dL / g.

[0018] The solid-phase thickening temperature is 200-260℃, and the endpoint of thickening is an intrinsic viscosity ≥3.0 dL / g. The solid-phase thickening temperature is generally 20-30℃ below the melt Tm. After modification, the resin melting point decreases, and the solid-phase thickening temperature also decreases to 200-260℃. Due to the reduced intermolecular order, the melt viscosity also decreases. Therefore, an intrinsic viscosity ≥3.0 dL / g is set as the endpoint of solid-phase thickening.

[0019] The beneficial effects of this invention are: This invention incorporates 3-ethoxy-4-hydroxybenzoic acid (EHA) as a novel polymerizing monomer into thermotropic liquid crystal polymers (TLCPs). This represents a strategic innovation that sacrifices secondary properties (absolute strength) to overcome a core bottleneck in TLCP processing. This invention achieves three key breakthroughs through controllable strength loss: First, a breakthrough in processability—the reduced viscosity allows for the injection molding of ultra-thin-walled parts using TLCPs, meeting the cutting-edge demands of 5G micro-connectors and wearable device chip supports. Second, improved reliability—significantly increased impact strength reduces the risk of drop cracking while also improving weld line strength. Third, optimized overall cost—improved flowability reduces injection pressure and extends mold life.

[0020] This invention achieves targeted regulation of TLCP material properties by precisely controlling the introduction method and proportion of EHA, and successfully develops a high-performance material with excellent processing fluidity, good toughness and controllable mechanical strength. It effectively solves the technical problems of high processing temperature and fragile weld lines of traditional TLCP, and shows broad potential in high-precision application fields such as microelectronic components and medical devices. Detailed Implementation

[0021] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0022] To enable those skilled in the art to better understand the technical solution of this application, the technical solution of this application will be described in detail below with reference to specific embodiments.

[0023] The test materials used in the embodiments of this invention, unless otherwise specified, are all conventional test materials in the art and can be purchased through commercial channels. The CAS number of 3-ethoxy-4-hydroxybenzoic acid (EHA) used in this invention is 5438-38-0. The CAS number of antimony acetate used is 6923-52-0. The solid-phase polymerization apparatus used is an RS-SSP-5L manufactured by Zhangjiagang Rongsheng Machinery Co., Ltd.

[0024] Examples 1-10 HBA, EHA and HNA were used to prepare a thermotropic liquid crystal polymer with low viscosity and high strength according to the monomer ratios in Table 1.

[0025] Table 1 Monomer ratios for each embodiment The specific preparation method is as follows: First, the monomer and antimony acetate catalyst were mixed evenly in a specific ratio. Then, acetic anhydride, used as an acetylation reagent, was added. The amount of antimony acetate added was 300 mg / kg relative to the total mass of monomer used, and the molar ratio of acetic anhydride to monomer was 1.1:1. Subsequently, under an inert gas atmosphere maintained by 99.9% high-purity nitrogen, heating and stirring were started. The stirring rate was 50 rpm / min. When the temperature reached 150°C, the solid material completely melted, and the acetylation reaction began. The reaction continued for 1 hour, yielding a mixture of acetylated monomer and unreacted acetic anhydride. Next, the temperature was gradually increased and distilled off the unreacted acetic anhydride and the polymerization byproduct acetic acid, promoting the forward polymerization reaction by removing the byproduct. The temperature was then further increased, reacting at 200°C for 1 hour, 220°C for 1 hour, and 280°C for 2 hours, respectively. Afterward, the temperature was raised to 320°C, and a vacuum was drawn to -0.1 MPa, continuing the reaction for 1 hour to obtain the prepolymerized product. Finally, the prepolymer was placed in a solid-state viscosity-enhancing device and reacted under vacuum at 200°C for 24 hours to obtain a thermotropic liquid crystal polymer with low viscosity and high strength.

[0026] Comparative Examples 1-11 Comparative Example 1 uses HBA (73 mol%) and HNA (27 mol%) as the composition ratio of TLCP. This composition ratio is that of a classic brand, with excellent performance and wide application, and is suitable for improvement based on this.

[0027] Vanillic acid is a chemical monomer with a structure similar to EHA. Comparative Examples 2-11 used vanillic acid as a component other than HBA and HNA to prepare thermotropic liquid crystal polymers. The preparation method was the same as in Examples 1-10, and the monomer ratios of each comparative example are shown in Table 2.

[0028] Table 2. Monomer Ratios for Each Comparative Example The preparation method of thermotropic liquid crystal polymers is as follows: First, the monomer and antimony acetate catalyst were mixed evenly in a specific ratio. Then, acetic anhydride, used as an acetylation reagent, was added. The amount of antimony acetate added was 300 mg / kg relative to the total mass of monomer used, and the molar ratio of acetic anhydride to monomer was 1.1:1. Subsequently, under an inert gas atmosphere maintained by 99.9% high-purity nitrogen, heating and stirring were started. The stirring rate was 50 rpm / min. When the temperature reached 150°C, the solid material completely melted, and the acetylation reaction began. The reaction continued for 1 hour, yielding a mixture of acetylated monomer and unreacted acetic anhydride. Next, the temperature was gradually increased and distilled off the unreacted acetic anhydride and the polymerization byproduct acetic acid, promoting the forward polymerization reaction by removing the byproduct. The temperature was then further increased, reacting at 200°C for 1 hour, 220°C for 1 hour, and 280°C for 2 hours, respectively. Afterward, the temperature was raised to 320°C, and a vacuum was drawn to -0.1 MPa, continuing the reaction for 1 hour to obtain the prepolymerized product. Finally, the prepolymer was placed in a solid-state viscosity-enhancing device and reacted under vacuum at 200°C for 24 hours to obtain a thermotropic liquid crystal polymer with low viscosity and high strength.

[0029] Experimental Example 1 The thermotropic liquid crystal polymers obtained in Examples 1-10 and Comparative Examples 1-11 were subjected to performance tests, including cantilever beam notched impact strength, tensile strength, and melt viscosity (350℃ 1000s). -1 The test standards for cantilever beam notched impact strength were ISO 180, tensile strength were ISO 527-2, and melt viscosity were GB / T25278-2010 "Determination of flowability of plastics by capillary and slit-die rheometer". The results are shown in Table 3.

[0030] Table 3 Performance comparison of each embodiment and comparative example According to the data in Table 3, for Examples 1-5, when EHA was used to replace part of the HNA, the tensile strength of the material only decreased slightly, while the notched impact strength increased significantly, and the melt viscosity also decreased significantly. The slight decrease in tensile strength can be attributed to the reduction of rigid groups in the molecular chain: the naphthalene ring contained in HNA has a high rigidity and linear symmetry structure, which can significantly enhance intermolecular forces and packing density; while the benzene ring in the EHA structure is relatively small, and its flexible ethoxy group weakens the inter-chain interaction. The significant increase in notched impact strength is due to the introduction of the ethoxy group, which gives the molecular chain local mobility, allowing the impact energy to be dissipated through micro-Brownian motion. At the same time, the decrease in polymer crystallinity and the increase in the proportion of amorphous regions make the crack propagation path more tortuous. The significant decrease in melt viscosity is due to the fact that the EHA side chain disrupts the chain segment regularity, weakens the intermolecular forces, and thus enhances the chain segment mobility at the same processing temperature. For Examples 6-10, when EHA was used to replace part of the HBA, the mechanical properties of the material decreased significantly, but the melt viscosity was greatly reduced, which provides a key process advantage for precision injection molding of thin walls and complex structures.

[0031] Comparing the data from the examples with the corresponding comparative data clearly shows that, at the same replacement ratio, replacing the corresponding amount of EHA with vanillic acid results in a systematic deterioration in the improvement of tensile strength, impact toughness, and melt flowability. This difference mainly stems from subtle differences in their chemical structures: the methoxy group in vanillic acid is less reactive than the ethoxy group in EHA, potentially leading to lower polymerization efficiency and a wider molecular weight distribution, resulting in a more significant strength loss. Simultaneously, the shorter methoxy chain and lower degree of freedom of movement weaken its ability to toughen and reduce melt viscosity, limiting the improvement in impact strength and making the flowability improvement less pronounced than with EHA. Furthermore, the poor thermal stability of the methoxy group makes it more prone to degradation during high-temperature processing, further affecting material properties. Therefore, EHA, with its superior reactivity, longer flexible side chains, and higher thermal stability, can more effectively improve toughness and flowability while controlling the loss of mechanical properties, making it a more ideal monomer choice for TLCP modification.

[0032] This invention achieves three core breakthroughs through controllable strength loss: First, a breakthrough in processability, with reduced viscosity enabling TLCP to be used for injection molding of ultra-thin-walled parts, meeting cutting-edge demands such as 5G micro-connectors and wearable device chip brackets. Second, improved reliability, with increased impact strength significantly reducing the risk of drop cracking while also improving weld line strength. Third, optimized overall cost, with improved flowability reducing injection pressure and extending mold life.

[0033] Adding 3-ethoxy-4-hydroxybenzoic acid (EHA) as a novel monomer to thermotropic liquid crystal polymers (TLCPs) is a strategic innovation that sacrifices secondary properties (absolute strength) to overcome the core bottleneck of TLCP processing. This invention achieves targeted regulation of TLCP material properties by precisely controlling the introduction method and proportion of EHA, and successfully develops a high-performance material with excellent processing fluidity, good toughness, and controllable mechanical strength. It effectively solves the technical problems of high processing temperature and fragile weld lines in traditional TLCPs, and shows broad potential in high-precision application fields such as 5G connectors, microelectronic components, and medical devices.

[0034] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A low-viscosity, high-strength thermotropic liquid crystal polymer, characterized in that, It is polymerized from monomers including p-hydroxybenzoic acid, 3-ethoxy-4-hydroxybenzoic acid, and 2-hydroxy-6-naphthoic acid.

2. The low-viscosity, high-strength thermotropic liquid crystal polymer according to claim 1, characterized in that, 3-Ethoxy-4-hydroxybenzoic acid accounts for 1-5 mol of the total structural units in the polymer backbone.

3. The low-viscosity, high-strength thermotropic liquid crystal polymer according to claim 1, characterized in that, In terms of molar percentage, the ratio of p-hydroxybenzoic acid to 2-hydroxy-6-naphthoic acid in the polymer backbone structural unit is (68-73):(22-26).

4. The low-viscosity, high-strength thermotropic liquid crystal polymer according to claim 1, characterized in that, The performance indicators of the low-viscosity, high-strength thermotropic liquid crystal polymer are as follows: notched cantilever beam impact strength is 20.4-50.2 J / m, tensile strength is 92.3-121.4 MPa, and melt viscosity is 3.61-8.04 Pa·s.

5. The method for preparing the low-viscosity, high-strength thermotropic liquid crystal polymer according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Mix the monomer and catalyst evenly according to the ratio, and add acetic anhydride; (2) Heating and stirring are carried out in an inert atmosphere until the solid material is completely melted. The temperature is maintained to carry out the acetylation reaction. (3) Continue heating to promote the forward polymerization reaction and obtain the prepolymer; (4) The prepolymer is added to a solid-phase thickening device to carry out a thickening reaction, and a low-viscosity, high-strength thermotropic liquid crystal polymer is obtained.

6. The method for preparing low-viscosity, high-strength thermotropic liquid crystal polymer according to claim 5, characterized in that, In step (1), the catalyst used is antimony acetate. Compared with the total mass of the monomers used, the amount of antimony acetate catalyst added is 200-400 mg / kg; the molar ratio of the added acetic anhydride to the monomer is (0.8-1.2):

1.

7. The method for preparing low-viscosity, high-strength thermotropic liquid crystal polymer according to claim 5, characterized in that, In step (2), 99.9% high-purity nitrogen is used to maintain an inert atmosphere, the stirring rate is 20-100 rpm / min, and the temperature is maintained at 140-160℃ for 0.5-2 hours.

8. The method for preparing low-viscosity, high-strength thermotropic liquid crystal polymer according to claim 5, characterized in that, In step (3), the temperature is increased and the reaction is carried out at 190-210℃ for 0.5-2 hours, 210-230℃ for 0.5-2 hours, and 270-290℃ for 1-3 hours. Then the temperature is increased to 310-330℃, the vacuum is evacuated to -0.1 MPa, and the reaction is continued for 0.5-2 hours to obtain the prepolymer.

9. The method for preparing low-viscosity, high-strength thermotropic liquid crystal polymer according to claim 5, characterized in that, In step (4), the prepolymer is subjected to a vacuum reaction at 190-210°C for 12-36 hours in the solid phase thickening device.

10. The method for preparing low-viscosity, high-strength thermotropic liquid crystal polymer according to claim 5, characterized in that, In step (4), after the thickening reaction, the melt viscosity of the low-viscosity, high-strength thermotropic liquid crystal polymer is ≥3.0 dL / g.

Citation Information

Patent Citations

  • Main chain type liquid crystal polyester, liquid crystalline composition, method for producing liquid crystal film, optical film and display

    CN1522268A

  • Thermotropic liquid crystal copolyester

    JP1988132933A

  • Liquid crystalline polyester and optical film

    JP2004292490A

  • Thermotropic liquid crystal polyester

    JP2012116913A

  • Liquid crystalline resin and liquid crystalline resin composition, and molding thereof

    JP2023135620A